1998
DOI: 10.1128/jcm.36.10.3066-3069.1998
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of Nosocomial Transmission of Hepatitis C Virus by Phylogenetic Analysis of the NS5-B Region

Abstract: Four hepatitis C virus transmission chains at three dialysis units were disclosed by limited sequencing; three of these were disclosed by analysis of the NS5-B region of the genome. Dialysis on the same shift as that during which infected patients were dialyzed was the common factor for seven patients in two chains. Two nurses exposed to needle sticks and their sources of infection constituted two other chains. The strains of three chains belonged to subtype 1a and formed clusters with an intrachain variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(17 citation statements)
references
References 21 publications
(31 reference statements)
0
16
1
Order By: Relevance
“…Japan have revealed nosocomial HCV infection in haemodialysis units using phylogenetic analysis of different sequences of the HVR-1 region [Mizuno et al, 1998;Iwasaki et al, 2000]. Nosocomial transmission was also shown by sequencing the NS5B region [Le Pogam et al, 1998;Norder et al, 1998]. Nevertheless, sequencing the HVR-1 region confirmed these results, as this very variable region was identical in two HCV isolates we conclude that it was the same viral isolate.…”
Section: Discussionmentioning
confidence: 59%
“…Japan have revealed nosocomial HCV infection in haemodialysis units using phylogenetic analysis of different sequences of the HVR-1 region [Mizuno et al, 1998;Iwasaki et al, 2000]. Nosocomial transmission was also shown by sequencing the NS5B region [Le Pogam et al, 1998;Norder et al, 1998]. Nevertheless, sequencing the HVR-1 region confirmed these results, as this very variable region was identical in two HCV isolates we conclude that it was the same viral isolate.…”
Section: Discussionmentioning
confidence: 59%
“…cDNA of all samples found positive by 5 H UTR PCR were subjected to another PCR within the NS5B region with primers hep-101 at position 8258 and hep-120 (5 H -TGCGCGACBGABACRTTKGAGGA-3 H ) at position 8687. The product was nested with primers hep-101 and hep-105 as described [Norder et al, 1998]. The NS5B region of ®ve strains, which could not be ampli®ed with the outer primers mentioned, were ampli®ed with outer primers hep-106 (5 H -GCTCNT-AYGGRTTYCARTACTC-3 H ) at position 8155 and hep-105.…”
Section: Rna Extraction and Cdna Synthesismentioning
confidence: 99%
“…While the HVR1 sequence comparison clearly and sensitively showed the phylogenetic relationships in HCV transmission [13,22±24], the obscure clustering in this study, on the contrary, revealed the limitations of phylogenetic analysis using HVR1 sequences. Other relatively variable regions, such as E1 and NS5 [16,17,25], should be examined in a similar manner to con®rm these clusters.…”
Section: ) 6a --Ht---a--ft-hrf--mf T---------(1) 6b --Ht---v-g F--rrfmentioning
confidence: 99%
“…Several investigators have reported nosocomial transmission of HCV, among haemodialysis patients, using similar molecular evolutionary analyses [12±17, 23,26]. They also demonstrated that patient-to-patient transmission occurred more frequently within the same treatment shift than within the same consoles [12,13,25]. A clear mode of HCV transmission among haemodialysis patients has not been established, but HCV was probably carried by the medical staff rather than on haemodialysis consoles or in the environment [27,28].…”
Section: ) 6a --Ht---a--ft-hrf--mf T---------(1) 6b --Ht---v-g F--rrfmentioning
confidence: 99%